Transdermal Delivery Of Aceclofenac: Effect Of Piperine And Its Mechanism Of Action - KAPIL K. SHAH,; MAHENDRA R. SHIRADKAR,; V. HIMA BINDU, (International Journal of Pharma and Bio Sciences, 2011)
Piperine, an amide alkaloid of black pepper, was investigated for transdermal enhancer activity using human cadaver skin in vitro with aceclofenac as the model drug. Furthermore, FT-IR studies were conducted to understand to possible enhancement mechanism. Piperine, at all three concentrations tested, significantly increased flux of the drug compared to control (p<0.05). Similarly permeability coefficient (Kp), cumulative amount release (Q24) and enhancement ratio (ER) shown significant increase over control sample whereas skin content of aceclofenac and lag-time of enhancer treated epidermal membrane shown proportionate reduction over control. FT-IR studies reveal that piperine reduces peak area by 19.17 % and 16.87 % for symmetric and asymmetric stretching peaks. In addition, piperine significantly reduces percentage of secondary structures of keratin at amide I band. These results indicate that piperine enhances transdermal permeation of aceclofenac by biphasic mechanism involving partial extraction of stratum corneum (SC) lipid and interaction with SC keratin.